History of the liturgy : the major stages - Metzger, Marcel; Beaumont, Madeleine (Collegeville, Minnesota : Liturgical Press, 1997)
"How great the differences between the Last Supper celebrated by Jesus and a pontifical high Mass at St. Peter's in Rome - and also between the early baptisms by immersion described in the Acts of the Apostles and the baptisms of babies in our parishes! Why such a change in the celebration of the Christian mystery? Why the recent reforms, often poorly understood? We can understand this evolution only through a carefully documented historical survey, like the one the author offers in this book." "Marcel Metzger describes the most important phases of this evolution. Throughout the first millennium, it is in its essentials common to the Eastern and Western churches. For the second millennium, the historian must explain the deviations of the Western churches that urgently called for the reform and renewal initiated by Vatican II." "This clear and precise exposition is designed to awaken readers' interest in the realities that have made and still make up the Church's liturgical life: assemblies, Eucharist, baptism, reconciliation, daily praise . . . but also the Church's calendar and its architecture."--BOOK JACKET.
Includes bibliographical references
Keywords: Catholic Church -- Liturgy -- History and criticism; Liturgics